Atomistic simulation of amorphous carbon nanowires - Low, Shao Jun (2014)
Carbon Nanotubes (CNTs) have been widely recognized for its industrial applications such as energy storage, water filters, actuators, etc. Their popular usage has resulted in the production of several thousand tons per year as of 20131. CNTs are well known for their extraordinary mechanical, thermal and electrical properties. Their remarkable applications have justified the cause of current evolving research and large investments in its synthesis over the last decade. It is constantly of interest to discover new approaches which increases synthesis efficiency and optimizes CNT production. Current technology proposes gas phase synthesis of CNTs – they include Chemical Vapour Deposition (CVD), arc discharge and laser ablation. CNTs have been produced recently by transformation of disordered carbon structures such as amorphous carbon nanowires and glass-carbon nanoparticles2-5. Amorphous carbon nanowires are able to transform to ordered sp2-hybridized structures under high temperature. The extent of transformation depends on other variables such as density of the amorphous carbon and the heating rate. The dependence of the mentioned variables have not been researched extensively and present a meaningful cause for the current project to be conducted.